2004
DOI: 10.1155/2004/595470
|View full text |Cite
|
Sign up to set email alerts
|

A Canadian Clinical Practice Algorithm for the Management of Patients with Non-Variceal Upper Gastrointestinal Bleeding

Abstract: This algorithm should facilitate appropriate risk stratification, use of endoscopic therapy and the appropriate utilization of proton-pump inhibition to optimize the care of patients with upper gastrointestinal bleeding. The algorithm should be customized to the resources of individual medical centres. Its application should be studied with appropriate outcomes recorded and validation performed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
17
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(17 citation statements)
references
References 60 publications
0
17
0
Order By: Relevance
“…The causes of UGIB have been classified into variceal bleeding (esophageal and gastric varices) and non-variceal bleeding (peptic ulcer, erosive gastroduodenitis, reflux esophagitis, tumor, vascular ectasia, etc). Currently, emergency esophagogastrodu odenoscopy (EGD) is the standard investigation of choice for active UGIB since it provides both diagnosis and treatment of UGIB [2][3][4][5][6][7][8][9][10][11] . However, in the real life situation, emergency EGD is seldom available in most hospitals due to the difficulty of setting up emergency services in non-official time, an insufficiency of well-trained endoscopists and medical teams and lack of equipment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The causes of UGIB have been classified into variceal bleeding (esophageal and gastric varices) and non-variceal bleeding (peptic ulcer, erosive gastroduodenitis, reflux esophagitis, tumor, vascular ectasia, etc). Currently, emergency esophagogastrodu odenoscopy (EGD) is the standard investigation of choice for active UGIB since it provides both diagnosis and treatment of UGIB [2][3][4][5][6][7][8][9][10][11] . However, in the real life situation, emergency EGD is seldom available in most hospitals due to the difficulty of setting up emergency services in non-official time, an insufficiency of well-trained endoscopists and medical teams and lack of equipment.…”
Section: Introductionmentioning
confidence: 99%
“…Some practice guidelines on non-variceal bleeding [5,6] , variceal bleeding [12,13] including Thai guidelines in 2004 [14] recommend giving empirical treatments to patients with UGIB while waiting for EGD. If variceal bleeding is suspected, empirical treatment with vasoactive agents (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…At the time of randomization, lead investigators at both control and experimental sites received the guidelines 1 and the corresponding algorithm 8 on the care of patients with nonvariceal upper gastrointestinal bleeding, adapted to Canadian practice. The experimental group also received a multifaceted intervention; its specific components were determined following a national analysis of needs and barriers.…”
Section: Study Interventionsmentioning
confidence: 99%
“…11 During months 4-5, a 2-hour collaborative care workshop was held, with the aim of producing an institution-specific management algorithm using a published template. 8 …”
Section: Study Interventionsmentioning
confidence: 99%
“…2,3 Previous studies have suggested that a lower hemoglobin threshold for red cell transfusion can be safe and effective, but those studies did not include patients with gastrointestinal bleeding. 4,5 Current Canadian guidelines for management of nonvariceal upper gastrointestinal bleeding fail to address a hemoglobin threshold for red cell transfusion, 6 whereas British guidelines for the same suggest red cell transfusion whenever hemoglobin concentration falls below 100 g/L. 7 There have been no studies that directly assess whether a restrictive threshold for red cell transfusion in patients with acute upper gastrointestinal bleeding is more effective than a liberal transfusion strategy.…”
mentioning
confidence: 99%